Safety assessment of the ethanol extract of Caesalpinia bonduc (L.) Roxb. Root in Wistar rats: Acute and subacute (28-day) oral toxicity studies - Sindete, Mariette; YEMOA, Achille (My University, 2019)
Background: Caesalpinia bonduc (CB) root is used in African Pharmacopoeia for the prevention and treatment of sexual failure. Aims and Objective: The current study performed to evaluate the acute and subacute oral toxicity of the ethanolic extract of CB root. Materials and Methods: Two groups of three female Wistar rats were used for acute oral toxicity test. A single dose of 2000 mg/kg body weight (BW) of the ethanolic extract of CB root was administered to the test group; the control group received dimethyl sulfoxide. Rats were observed individually during the first 4 h and then daily until days 14. For subacute toxicity model, the male rats were divided into four groups (n = 6). Experimental groups received 31, 25, 125, and 500 mg/kg of BW of the ethanolic extract of CB root orally daily for 28 days. The blood hematological and biochemical parameters, as well as histopathology of liver and kidneys, were studies. Results: No toxicological signs were observed in rats when acutely exposed to the ethanolic extract of CB root. After the repeated administration of CB root extract, hematological and biochemical parameters were unaltered except hemoglobin and erythrocyte number in the exposed animal, but they were considered to be temporary effects and not an indication of toxic effects. No macroscopic changes and no noticeable histological changes were seen in the histopathology analysis of kidneys and liver. Conclusion: Ethanolic extract of CB root at single dosage level up to 2000 mg/Kg BW is nontoxic and can show protection of some vital organs when administered to 28 days.
Keywords: Caesalpinia bonduc; Wistar Rat; Acute Toxicity; Subacute Toxicity; Histopathology